The Phospholipase A2 Homologues of Snake Venoms: Biological Activities and Their Possible Adaptive Roles - Lomonte, Bruno (2009)
A particular subgroup of toxins with phospholipase A2 (PLA2) structure, but devoid of this enzymatic activity, is commonly found in the venoms of snakes of the family Viperidae, and known as the PLA2 homologues. Among these, the most frequent type presents a lysine residue at position 49 (Lys49), in substitution of the otherwise conserved aspartate (Asp49) of catalytically-active PLA2s. A brief and updated overview of these toxic PLA2 homologues is presented, emphasizing their various biological activities, both in vivo and in vitro. The relevance of these bioactivities in relation to their possible adaptive roles for the snakes is discussed. Finally, experiments designed to assess the validity of such hypothetical roles are suggested, to stimulate future studies in this field.